UPAYA MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA PADA ANAK TUNAGRAHITA RINGAN MELALUI JOYFUL LEARNING STRATEGY (Classroom Action Research Kelas III di SLB Al-Azhar Bukittinggi) - Nelfa Zulhas (Jurnal Penelitian Pendidikan Khusus, 2016)
Abstract: This research is based on the problem that was found in SLB AL-Azhar Bukittinggi on the mild mental retardation kids grade III who had less interest and motivation to learn math. The students tend to be passive and only listening during the class, they were also looks less enjoy the lesson. It influenced the learning goal and the outcomes will not be maximum. The goal of this research is to know whether joyful learning strategy can increase the motivation to learn Math of the mild mental retardation kids grade III in SLB Al-Azhar Bukittinggi. The research method being used was classroom action research that consist of II cycles. Each consist of 5 meetings and carried out in several stages, that were action planning, implementation, observation, and reflection. The data collection techniques were observation, interview, and documentation. The observation result of the analysis of the students initial capability was with the average RA 28% and RZ 35%. After the cycle I was done, it became RA 65% and RZ 62%. And it increased again after the cycle II was done, the average increased to RA 81% and RZ 77%. The result shows that joyful learning strategy can increase the motivation to learn Math on mild mental retardation kids grade III in SLB Al-Azhar Bukittinggi.  Kata kunci: motivasi belajar matematika; joyful learning stategy; anak tunagrahita ringan